The Roles of Injury Type, Injury Level and Amputation Type in the Need for Revision Surgery after Replantation: Retrospective Clinical Outcome with 296 Finger Replantation - Burak Sercan Erçin; Burak Ergün Tatar; Musa Kemal Keleş; Fatih Kabakaş (Journal of Investigative Surgery, 2022)
Background With the development of microsurgical techniques, the replantation survival rate has increased, but in some cases, revision surgery is required. Although there are many studies on replantation survival rate, studies on revision surgery are limited. In this study, we evaluated replantation patients requiring revision surgery in terms of amputation level, injury type, and amputation type (single-multiple). Methods This is a retrospective study.Two hundred fifty-six patients (296 fingers) who were operated on for total finger amputation in our hospital between 2013 and 2018 were included in the study. In the postoperative period, revision surgery was required for 24 fingers due to vascular insufficiency. Patients were evaluated in terms of amputation level, injury type, and amputation type. Results Two hundred sixty-four fingers were saved after primary surgery. Eight fingers failed before they could undergo revision surgery. Revision surgery was performed for 24 fingers. After revision surgery, 19 fingers were saved, and five fingers were failed. There was no significant effect of gender and age in terms of revision (p > 0.05).There was no statistically significant difference in injury level and injury type, but there was a statistically significant difference in terms of amputation type (p < 0.05). Conclusion Despite advanced microsurgery and experience, vascular insufficiency can be observed after replantation. Surgical re-exploration is necessary for salvage.